Distribution and flower visitation records of bumblebees in Lebanon (Hymenoptera: Apidae). Issue 2 (3rd March 2020) - Boustani, Mira; Yammine, Wael; Nemer, Nabil; Abou Fakhr Hammad, Efat; Michez, Denis; Rasmont, Pierre
Summary: West Palearctic bumblebees are common wildflowers and crop pollinators that are well studied in their central and northern distribution ranges, but fewer information is available on their southern distribution areas. Lebanon falls on the southern limit of their distribution and no published information is available on the local bumblebees. Our study aims to produce a data baseline of the local bumblebee species. In order to do so we grouped available old records of bumblebees in Lebanon with recent author collections and produced preliminary distribution maps. We listed four species: Bombus terrestris, B. argillaceus, B. niveatus vorticosus and B. melanurus . Preliminary distribution shows that Bombus terrestris and B. argillaceus are widespread and have a large foraging range, whereas B. niveatus vorticosus and B. melanurus have a restricted distribution to altitudes above 1800 m with a smaller foraging range. The male cephalic labial gland secretions analysis of local Bombus terrestris specimens provides preliminary evidence that the local subspecies could be Bombus terrestris calabricus . Therefore, we highlight the importance of regulating foreign Bombus terrestris subspecies importation for agriculture purposes, as well as monitoring B. niveatus vorticosus and B. melanurus that are rendered vulnerable by their isolated populations.